Planetary omnibus - Ellis, Warren 1968- (DC Comics, 2014)
"PLANETARY has been hailed as a timeless story that turned modern superhero conventions on their heads. Written by Warren Ellis (TRANSMETROPOLITAN) and with stunning art by John Cassaday (Astonishing X-Men), this critically acclaimed, landmark series took a look at the inter-dimensional peace-keeping force known as Planetary. The trio on the ground includes Elijah Snow, a hundred-year-old man, Jakita Wagner, an extremely powerful woman, and The Drummer, a man with the ability to communicate with machines. Tasked with tracking down evidence of super-human activity, these mystery archaeologists uncover unknown paranormal secrets and histories, such as a World War II supercomputer that can access other universes, a ghostly spirit of vengeance, and a lost island of dying monsters. All 27 issues of the original series are collected in this hardbound omnibus edition"..
"Originally published in single magazine form as PLANETARY 1-27, PLANETARY/BATMAN, PLANETARY/JLA, PLANETARY/AUTHORITY"...T.p. verso
Keywords: Comic books, strips, etc; COMICS & GRAPHIC NOVELS / Science Fiction; Superheroes -- Comic books, strips, etc; Graphic novels; Superheld; Comic